A Review to Populate A Proposed Cost-Effectiveness Analysis of Glaucoma Screening in Sub-Saharan Africa. (4th May 2022) - Olawoye, Olusola; Azuara-Blanco, Augusto; Chan, Ving Fai; Piyasena, Prabhath; Crealey, Grainne E.; O'Neill, Ciaran; Congdon, Nathan
ABSTRACT: To populate a proposed cost-effectiveness analysis of glaucoma screening in Sub-Saharan Africa (SSA). A complete search was conducted on PubMed, Medline and African Journals Online (AJOL) to obtain relevant published articles, which were included in this review. All relevant articles on prevalence of glaucoma in SSA and among other African-derived populations, severity of glaucoma, cost of diagnosis and management, clinical effectiveness of glaucoma screening and treatment and the different glaucoma screening strategies in SSA were reviewed. Population screening interventions for glaucoma may be considered as follows: standalone screening for glaucoma, screening for glaucoma during cataract outreach, and screening incorporated with diabetic retinopathy image review using tele-ophthalmology. Our review suggests that cost of glaucoma treatment is relatively low with cost of medical treatment ranging from USD 273 to USD 480 per year/patient and surgical treatment cost of USD 283 per patient as with other developing countries. Compliance with medication is moderate to good in about 50% of glaucoma patients. Prevalence of glaucoma is much higher in SSA and almost 50% of glaucoma patients are blind in at least one eye at presentation in clinics (without outreach screening). Our review suggests a moderate sensitivity and specificity in identifying glaucoma with basic equipment (direct ophthalmoscope, contact tonometer and frequency doubling technology) during outreach screening although about a third or fewer take up glaucoma services in clinics. Our review provides the necessary information to conduct a cost-effective analysis of glaucoma screening in SSA using the decision Markov model.